ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI MANAJEMEN LABA DI SEPUTAR RIGHT ISSUE - PUJI ASTUTI, DEWI SAPTANTINAH (Jurnal Ilmiah Akuntansi dan Bisnis, 2007)
This research is aimed at analysing factors influencing the motivation of management toconduct earnings management activity around the timing of right issue, and investigatingwhether there are any differences between discretionary accruals before and after the right issue,that is the discretionary accruals tend to be high before the right issue than that of after the rightissue. Some factors influencing the motivation of earnings management used in this research areownership structures, consisted of institutional ownership, managerial ownership, leverage andsize; in this research size was included into controlled variable and earnings management wassubstituted (proxy) with discretionary accruals.The sample of this research consists of companies conducting the right issue between theyear of 1998-2001, with 2 years observation period before and after the right issue. Therefore,the period included in this research is 1996-2003. Hypothesis testing is conducted usingregression, while pair t-test is used to investigate the differences of discretionary accruals beforeand after the right issue. The result shows that leverage influences the earnings managementpositively and significantly. It means that the higher the leverage, the more the management ismotivated to conduct earnings management. In addition, the result of the study shows that thereare differences between discretionary accruals before the right issue and that of after the rightissue, i.e. the discretionary accruals before the right issue tends to be higher than that of after.
Keywords: management motivation, earnings management, ownership structure, leverage